Immune Cell Subtypes and Their Function in the Testis - Bhushan, Sudhanshu; Theas, María S.; Guazzone, Vanesa A.; Jacobo, Patricia; Wang, Ming; Fijak, Monika; Meinhardt, Andreas; Lustig, Livia (Frontiers in Immunology, 2020)
Immunoregulation in the testis is characterized by a balance between immuno-suppression (or immune privilege) and the ability to react to infections and inflammation. In this review, we analyze the phenotypes of the various immune cell subtypes present in the testis, and how their functions change between homeostatic and inflammatory conditions. Starting with testicular macrophages, we explore how this heterogeneous population is shaped by the testicular microenvironment to ensure immune privilege. We then describe how dendritic cells exhibit a tolerogenic status under normal conditions, but proliferate, mature and then stimulate effector T-cell expansion under inflammatory conditions. Finally, we outline the two T-cell populations in the testis: CD4+/CD8+ αβ T cells and CD4+/CD8+ Foxp3+ regulatory T cells. These cells help modulate innate immunity and regulate the immune response. By improving our understanding of immune cell behavior in the testis under normal and inflammatory conditions, we will be better placed to evaluate testis impairment due to immune mechanisms in affected patients.